A network pharmacology approach confirms Biejiaxiaozheng pills combat hepatic fibrosis by modulating macrophage inflammation and hepatic stellate cell activation - Weibin Wu; Yanli Liao; Jiefei Liang; Mi Huang; Guifeng Zhang; Yuying Hu; Chao Yuan; Duanzhou Li (Scientific Reports)
Abstract Biejiaxiaozheng (BJXZ) pills, a traditional Chinese medicine, have demonstrated anti-fibrotic effects; however, their mechanisms in treating liver fibrosis remain unclear. This study aimed to explore the active targets and underlying mechanisms of BJXZ pills using network pharmacology and experimental validation. Network pharmacology analysis identified 213 common drug-disease targets, 1131 Gene Ontology terms, and 163 signaling pathways (including the TNF pathway). Experimental results showed that BJXZ pills significantly suppressed LPS-induced viability increase in RAW264.7 macrophages by inhibiting NF-κB activation (p-P65), reducing INOS expression, and decreasing inflammatory cytokines. They also alleviated oxidative stress by upregulating Nrf2 and HO-1, restoring mitochondrial membrane potential, and enhancing ATP production. Additionally, BJXZ pills markedly inhibited TGF-β-induced activation of LX-2 hepatic stellate cells, reducing fibrotic markers like α-SMA. These findings suggest that BJXZ pills exert anti-fibrotic effects via multiple pathways, with the TNF pathway playing a key role. Mechanistically, the protective effects involve suppressing macrophage and hepatic stellate cell activation, highlighting BJXZ pills as a promising therapeutic option for liver fibrosis.